2002
DOI: 10.1093/jjco/hyf001
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Status and Expression of Human Telomerase Reverse Transcriptase mRNA in Relation to Hypermethylation of the p16 gene in Colorectal Cancers as Analyzed by Bisulfite PCR-SSCP

Abstract: Increased expression of hTERT is related to hypermethylation of hTERT in colorectal cancerous tissues as well as some cancer cell lines and disconcordant with hypermethylation of p16.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 17 publications
6
26
1
Order By: Relevance
“…This leads to progression into the S phase (31). Studies have indicated that telomerase activity is correlated with high expression of cyclin D and low expression of p16INK4 (32)(33)(34). In the present study, inhibition of hTERT expression significantly altered the cell cycle profile of H1299 cells; the proportion of cells in G1 was increased (to 73.9%), while the percentage of cells in S and G2 phases was decreased.…”
Section: Discussionsupporting
confidence: 41%
“…This leads to progression into the S phase (31). Studies have indicated that telomerase activity is correlated with high expression of cyclin D and low expression of p16INK4 (32)(33)(34). In the present study, inhibition of hTERT expression significantly altered the cell cycle profile of H1299 cells; the proportion of cells in G1 was increased (to 73.9%), while the percentage of cells in S and G2 phases was decreased.…”
Section: Discussionsupporting
confidence: 41%
“…In body fluids, including CSF, proliferating lymphocytes can be the cause of hTERT expression (16)(17)(18), which limits its use as a diagnostic tool in cancer. In contrast, hTERT promoter methylation is correlated with hTERT expression in most telomerase-positive tumors (19)(20)(21)(22), whereas the promoter is unmethylated in telomerase-positive-activated lymphocytes (23). Therefore, the use of hTERT methylation as a cancer biomarker might circumvent the confounding effect of activated lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Hypermethylation of hTERT was found to be necessary for its expression in cancer cells (3,8). The apparent opposition to the classic model of regulation was recently clarified by the observation that methylation plays a dual role (9,10).…”
Section: Introductionmentioning
confidence: 99%